Figures 1-20 from: Crabo L, Davis M, Hammond P, Mustelin T, Shepard J (2013) Five new species and three new subspecies of Erebidae and Noctuidae (Insecta, Lepidoptera) from Northwestern North America, with notes on Chytolita Grote (Erebidae) and Hydraecia Guenée (Noctuidae). ZooKeys 264: 85-123. https://doi.org/10.3897/zookeys.264.4304 - Crabo, Lars; Davis, Melanie; Hammond, Paul; Mustelin, Tomas; Shepard, Jon (Zenodo, 2013)
Figures 1-20 - Adults of Erebidae and Noctuidae. 1 Cycnia oregonensis tristis Crabo, male paratype, WA, Thurston Co., Plumb 2 Cycnia oregonensis oregonensis (Stretch), male, Canada, BC, 5 mi W of Nelson 3 Drasteria parallela Crabo & Mustelin, male paratype, WA, Chelan Co., Chumstick Mountain 4 Drasteria convergens Mustelin, male, CA, Mono Co., Lee Vining 5 Drasteria divergens (Behr), male, WA, Garfield Co., FR40 at Sunset Point 6 Eudryas brevipennis bonneville Shepard & Crabo, female paratype, ID, [Gooding Co.], Wendell 7 Eudryas brevipennis brevipennis Stretch, male, USA, CA, [Riverside Co.], Riverside 8 Eudryas unio (Hübner), male, USA, MA, Norfolk Co., Ponkapoag Bog 9 Resapamea diluvius Crabo, male paratype, WA, Grant Co., Potholes 10 Resapamea diluvius Crabo, female paratype, WA, Grant Co., Potholes 11 Resapamea diluvius Crabo, female paratype, WA, Adams Co., Washtucna 12 Resapamea passer (Guenée), male, Canada, SK, 2 mi N Burstall 13 Resapamea passer (Guenée), male, USA, WA, Island Co., Joseph Whidbey State Park 14 Resapamea passer (Guenée), female, USA, Douglas Co., Badger Mountain 15 Resapamea angelika Crabo, male holotype, USA, NV, Elko Co., Angel Lake 16 Resapamea innota (Smith), male, USA, OR, Lake Co., Bull Prairie 17 Resapamea mammuthus Crabo, male holotype, Canada, YT, Old Crow 18 Resapamea hedeni (Graeser), male, Russia, Magadan Oblast, Tenkinsky District, Stokovyi 19 Resapamea species, possibly Resapamea hedeni, female, USA, AK, Unalakleet 20 Resapamea species, possibly Resapamea mammuthus, female, Canada, NWT, Aklavik.